OCURRENCE OF Amblyomma spp. TICKS INFESTING Chironius bicarinatus, Bradypus tridactylus AND Puma concolor IN A ZOO OF MANAUS, AMAZONAS, NORTHERN BRAZIL - Somavilla Lignon, Julia; Martins, Thiago Fernandes; Tonin, Alexandre Alberto; Tochetto, Camila; Monteiro, Silvia Gonzalez (Archives of Veterinary Science, 2022)
Ticks are ectoparasites arthropods distributed worldwide that can parasitize a wide range of animals, and transmitting pathogens such as bacteria, protozoa, helminths and viruses. The species that parasitize domestic animals are the most studied due to their sanitary importance, but little is known about most of the tick species that parasitize wild animals. Therefore, the aim of this study is to report the ocurrence of tick’s parasitism of the genus Amblyomma infesting Vine-snake (Chironius bicarinatus), Bentinho’s Sloth (Bradypus tridactylus) and Puma (Puma concolor) in a zoo in the city of Manaus, Amazonas, northern Brazil. Larvae of the genus Amblyomma as well as specimens of A. ovale, A. varium and A. gaeyi were identified. Therefore, it is possible to say that these tick species are present in Manaus, Amazonas, as well as it is the first report of specimens of Amblyomma spp. parasitizing Chironius bicarinatus. The scarcity of reports of this nature highlights the need for further studies on the distribution of these arthropods in different regions and host species.